FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN MUSTAHIK ZAKAT PRODUKTIF - Arjuna Barona Aka; Amri Amri (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2022)
This study aims to determine the effect of demographic and socio-cultural factors on the welfare of productive zakat mustahik in Banda Aceh City. This study uses 7 variables, namely mustahik's welfare, family members, income, education level, age, empowerment, and religiosity. This research is a survey research using a questionnaire as an instrument. The population used in this study is the people of Banda Aceh City. The sample in this study were 100 people who were recipients of productive zakat funds in Banda Aceh Regency. Based on the results of multiple linear regression analysis shows that family members, education level, and age do not have a significant effect on the welfare of mustahik zakat productive in banda aceh. meanwhile, income, empowerment, and religiosity have a significant effect on the welfare of productive zakat mustahik in Banda Aceh.